Pengaruh Relaksasi Otot Progresif Dan Slow Deep Breathing Terhadap Penurunan Tingkat Kecemasan Pasien Pre Operasi Ca Mamae Di RSUD dr.Soenono Provinsi Jawa Timur - Putri Zhakia, Laila; Cahyo Sepdianto, Tri; Supono, Supono; Marsaid (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective:: Preoperative patients experience a lot of anxiety due to various factors that arise. The aim of this study was to determine the effect of progressive muscle relaxation therapy and slow deep breathing on reducing the anxiety level of pre-operative patients at Dr. Soedono Hospital, East Java province. Methods: The research design is Quasi experimental. The total research sample was 30 preoperative CA mammary patients. The interventions provided are Progressive Muscle Relaxation and Slow Deep Breathing. Anxiety levels were measured using a questionnaire. The analysis used is the bivariate Wilcoxon Sign Rank Test. Results:The results of the study showed that the level of anxiety before CA mammary surgery patients were given progressive muscle relaxation was 9(60%) seriously anxious and before the patients were given slow deep breathing 8(53.3%) were seriously anxious. After the intervention, 2 (13.3%) patients had the criteria for Severe Anxiety and in the slow deep breathing relaxation technique group 6 (40%) had the criteria for Severe Anxiety. Conclusion: There was an effect of progressive muscle relaxation therapy on reducing the anxiety level of preoperative CA Mamae patients with a p value. 0.001. After CA Mamae's pre-operative patient at Dr. RSUD. Soedono was given progressive muscle relaxation so his anxiety level was reduced because physical tension was reduced through muscle relaxation and induced a feeling of calm. Based on the research results, progressive muscle relaxation is recommended to reduce anxiety in preoperative CA mammary patients.